2019
DOI: 10.1002/ana.25439
|View full text |Cite
|
Sign up to set email alerts
|

Functional deficiency in endogenous interleukin‐1 receptor antagonist in patients with febrile infection‐related epilepsy syndrome

Abstract: Objective We recently reported successful treatment of a child with febrile infection‐related epilepsy syndrome (FIRES), a subtype of new onset refractory status epilepticus, with the recombinant interleukin‐1 (IL1) receptor antagonist (IL1RA) anakinra. On this basis, we tested whether endogenous IL1RA production or function is deficient in FIRES patients. Methods Levels of IL1β and IL1RA were measured in serum and cerebrospinal fluid (CSF). The inhibitory activity of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(132 citation statements)
references
References 49 publications
3
127
0
2
Order By: Relevance
“…Clarkson et al reported elevation of CSF IL‐1ra and IL1‐β in patients with FIRES, reduced expression of intracellular IL‐1ra isoforms, and a functional deficiency in IL‐1ra inhibitory activity. Although IL‐1β has been shown to play a critical role in epileptogenesis, CSF IL‐1β was low in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarkson et al reported elevation of CSF IL‐1ra and IL1‐β in patients with FIRES, reduced expression of intracellular IL‐1ra isoforms, and a functional deficiency in IL‐1ra inhibitory activity. Although IL‐1β has been shown to play a critical role in epileptogenesis, CSF IL‐1β was low in our study.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,26,27,37 Previous studies have reported that seizures can perpetuate inflammation, thus activating a vicious cycle that in turn fosters aberrant hyperexcitability contributing to seizure recurrence and severity. 38 Clarkson et al 39 reported elevation of CSF IL-1ra and IL1-β in patients with FIRES, reduced expression of intracellular IL-1ra isoforms, and a functional deficiency in IL-1ra inhib itory activity. Although IL-1β has been shown to play a crit ical role in epileptogenesis, CSF IL-1β was low in our study.…”
Section: Discussionmentioning
confidence: 99%
“…An important driver of fibrosis at the vasculature is the transforming growth factor beta (TGFβ), specifically involved in the epileptogenesis process and BBB dysfunction . A number of reports suggest a plethora of neurovascular therapeutic entry points, including anakinra, rapamycin, and losartan, supporting a venue for novel therapeutic, anti‐inflammatory or cerebrovascular repairing, approaches to the epileptic pathophysiology …”
Section: Discussionmentioning
confidence: 99%
“…50 A number of reports suggest a plethora of neurovascular therapeutic entry points, including anakinra, rapamycin, and losartan, supporting a venue for novel therapeutic, anti-inflammatory or cerebrovascular repairing, approaches to the epileptic pathophysiology. [50][51][52][53]…”
Section: Significance Of Perivascular Scar Pharmacologic Targetingmentioning
confidence: 99%
“…15 Compelling evidence exists that implicates IL cytokine system imbalance in FIRES patients. 9 Such imbalance caused by an intrinsic functional deficiency in endogenous IL1-RA activity will lead to an unopposed pathological inflammatory state, "a spark to the blaze," 5 driven by overactive IL-1β, a master cytokine of local and systemic inflammation and innate immunity. 16 The role of IL-1RA/ IL-1β pathway endowing genetic predisposition also comes from candidate gene analysis in children with FIRES.…”
Section: Pathogenesismentioning
confidence: 99%